PENGARUH KADAR AIR TERHADAP KUALITAS PELET KAYU DARI SERBUK GERGAJIAN KAYU JABON DAN KETAPANG - Ratri Yuli Lestari; I Dewa Gede Putra Prabawa; Budi Tri Cahyana (BRIN Publishing, 2019)
In the last few years, wood pellet demand has increased globally for residential purposes. In term of standard quality, wood pellet for residential purposes are tighter than industrial purposes. The wood pellet quality parameters are moisture changes in biomass, impacts on bulk density, and mechanical durability. This paper analyzes the effect of biomass moisture content (MC) into the quality of wood pellet made from jabon and ketapang sawdust to meet quality standard of ISO 17225-2. The pellet was grouped into three, based on MCs, i.e. <10% (air-dry), 15% and 20%. The sawdust was then pressed at 464.52 kg/cm2, 150°C for 10 minutes. Analysis of variance (ANOVA) was conducted by Tukey and Homogenity tests on results. The optimum wood pellet quality was assessed using scoring requirement for residential use with less smoke and combustion residue.